Can aid foster Africa's attainment of a just energy transition and external debt sustainability? - Kalimanshi Nsakaza; Talumba Ireen Chilipaine (Heliyon)
This study evaluated the relationship between Aid and Africa's potential to achieve the Just Energy Transition and external debt sustainability. In contrast to the instrumental variables technique, the paper employed a 2-step system GMM to analyze data from 39 African countries between 2012 and 2022. The paper also used 7 indicators of access to energy and electricity on both renewable and fossil fuels to measure the Just Energy Transition (JET) and 8 indicators to assess the external debt landscape of the sampled countries. The net official development assistance received per capital was used to measure foreign aid. The findings indicate that, for Africa, there was a significant and positive relationship between the net official development assistance and the energy sector for renewable energy, but an insignificant positive relationship for fossil fuels overall. This suggests that, while Net Official Development Assistance (ODA) inflow to Africa increased with the use of renewable energy, it did not significantly change with the use of fossil fuels. The findings also demonstrated that while interest payments on long-term external debt had a negative impact on ODA to African countries, the total external debt stock, mainly for Africa, had a positive and significant effect on the Net ODA received by the continent. The study concluded that in driving the JET, solar and bioenergy energy are a crucial renewable energy source for Africa that have the potential to revitalize the continent's renewable energy market as it. We recommend that Power market frameworks are a viable alternative that can be created by policymakers to promote and draw in private sector investment. Through innovative financing methods including securitization, blended finance, or public-private partnerships, the private sector can also use its knowledge of financial de-risking. For example, bonds backed by the cash flows from future renewable energy assets can be issued through securitization.